The Role Of Stakeholder In Increasing Costumer Interest In The iB Hijrah Haji Product at Bank Muamalat - Elvira Apriansi Dwi Nirmalasari; Agus Mahardiyanto; Duwi Yunitasari (Trunojoyo University of Madura, 2026)
This study aims to identify and analyze the role of stakeholder actors in increasing customer interest in the iB Hijrah Haji product at Bank Muamalat Jember Branch Office. This research is motivated by the decline in the number of hajj savings applicants at Bank Muamalat over the past four years. The approach used in the study is a mixed methods with the MACTOR method (Matrix of Alliance and Conflicts: Tactics, Objectives, and Recommendations). The results of this study indicate that actors in quadrant II with high influence and dependence, namely the Ministry of Religious Affairs and the Head of the Bank, have a strategic role in increasing customer interest in the iB Hijrah Haji product. Meanwhile, Marketing and Customer Service actors have high influence and low dependence, so they have the potential to encourage customer interest in the iB Hijrah Haji product without relying on the decisions of other actors. The strategies obtained include savings deposits, banking services, coordination with the Ministry of Religious Affairs, policy support by the Ministry of Religious Affairs, seminar involvement, customer approaches, customer follow-up, the role of IPHI, online reviews by customers, explanations of savings products, educational media, mobile services, promotions by product customers, providing digital services, making complaint records, product socialization, and partnering with external parties.Keywords: Stakeholders, MACTOR Analysis, Bank Muamalat